Recent Advances in Biodegradable Polymers - Dhamaniya, Sunil; Gupta, Virendrakumar; Kakatkar, Rucha (Journal of Research Updates in Polymer Science, 2018)
Biodegradable polymers are important as an alternative to conventional non-degradable polymers for sustainable eco-system. The recent trends indicate that the new developments in biodegradable polymers focus on novel polymer systems that can cater the need of biomedical and packaging applications in-terms of performance and economics. The new interest is rapidly moving toward reducing carbon footprint through utilization of carbon dioxide and developing new methods of manufacturing such as 3D printing for specific purposes. This review focus on the present state-of-art and recent developments in biodegradable polymers covering their sources, synthetic methodologies, salient properties, degradation patterns, polymer blends and nanocomposites. As well as biodegradable polymers as a 3D printing material and the use of carbon dioxide as a renewable raw material for biomedical and packaging applications.